Anti-staphylococcal activity of EW1, a traditional herbal remedy for carbuncles - Thirthagiri, Eswary; Ngeow, Yun Fong (Faculty of Medicine, University of Malaya, 2000)
A powder (EW1) made from a mixture of herbs used for the treatment of carbuncles by traditional medicine practitioners in China was investigated for anti staphylococcal activity by agar diffusion, time-kill studies and M.Le. determinations performed on 17 clinical isolates and a reference strain ATCC 29213. It was found that EW1 had little demonstrable ib vitro activity against the clinical isolates tested but inhibited the growth of the ATCC strain at 10 mg/l and retarded its growth in broth culture by an average of 1.5 log reduction in colony count.